Sex Education in the Trends of Contemporary Muslim Women's Da'wah Movements - Suhartini; Majid, Zamakhsyari Abdul; Ma’arif, Samsul; Rasyid, Daud; Hamid, Abdul; Uyuni, Badrah (International Journal of Science and Society, 2025)
This research explores and develops new theories about the trends of the contemporary Muslimah da'wah movement in building Sakinah, Mawaddah, and Rahmah families in Indonesia. Using a qualitative approach with descriptive methods, this research explores the concepts, strategies, and patterns of da'wah used by the Muslimah da'wah movement in building Islamic family resilience, namely sakinah, mawaddah, and rahmah families. The result of this research is that the concept of sakinah, mawaddah, and rahmah family used by the Muslimah da'wah movement refers to QS. ar-Rūm: 21 is not clear, especially the aspect of mawaddah so that it has an impact on the da'wah movement which includes elements and also management of building a sakinah, mawaddah and rahmah family. This can be seen in the imbalance in the distribution of da'wah materials, especially those related to sex education and husband and wife relationships in the family. Sex education and healthy interaction or behavior of husband and wife as an integral part of da'wah can provide positive input for the family. The collaboration of social media with formal and non-formal education in stages by including family sciences in the curriculum is needed to help individuals internalize religious values, facilitate deeper understanding, and stimulate spiritual reflection in the family.